2017
DOI: 10.1016/j.annemergmed.2017.07.372
|View full text |Cite
|
Sign up to set email alerts
|

301 Barriers to Prescribing Stroke Prophylaxis for Atrial Fibrillation in the Emergency Department: A Qualitative Provider Perspective

Abstract: Study Objectives: Current guidelines recommend oral anticoagulation (OAC) to reduce stroke risk in high-risk atrial fibrillation (AF) patients. However, emergency department (ED) prescribing is inconsistent. The provider factors influencing OAC prescribing in the ED are unknown. This study aimed to identify factors that prevent and support OAC prescribing for AF by ED physicians.Methods: These results are part of a larger study to identify barriers to optimal atrial fibrillation management in the ED at a terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…1 A recent US qualitative study of emergency physicians identified a similar list of prescribing barriers with 1 addition: the need for ED-specific AFF guidelines. 2 The rationale is that with certain acute conditions, such as AFF, both the ED patient population and the disease-management questions differ from those encountered by outpatient providers sufficiently to warrant ED-focused guidance. This would require the involvement of emergency physicians on the writing committees, as done by the Canadian Cardiovascular Society for their ED-management algorithm for AFF.…”
Section: To the Editormentioning
confidence: 99%
“…1 A recent US qualitative study of emergency physicians identified a similar list of prescribing barriers with 1 addition: the need for ED-specific AFF guidelines. 2 The rationale is that with certain acute conditions, such as AFF, both the ED patient population and the disease-management questions differ from those encountered by outpatient providers sufficiently to warrant ED-focused guidance. This would require the involvement of emergency physicians on the writing committees, as done by the Canadian Cardiovascular Society for their ED-management algorithm for AFF.…”
Section: To the Editormentioning
confidence: 99%